2004
DOI: 10.1523/jneurosci.2931-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

The Mental Retardation Protein PAK3 Contributes to Synapse Formation and Plasticity in Hippocampus

Abstract: Mutations of the gene coding for PAK3 (p21-activated kinase 3) are associated with X-linked, nonsyndromic forms of mental retardation (MRX) in which the only distinctive clinical feature is the cognitive deficit. The mechanisms through which PAK3 mutation produces the mental handicap remain unclear, although an involvement in the mechanisms that regulate the formation or plasticity of synaptic networks has been proposed. Here we show, using a transient transfection approach, that antisense and small interferin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
150
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(158 citation statements)
references
References 41 publications
8
150
0
Order By: Relevance
“…46 For PAK3 (p21-activated kinase), a member of PAK protein family that are activated by the two small RhoGTPases Rac and Cdc42 (cell division cycle 42 ), the contribution in synapse formation and plasticity was clearly demonstrated by two groups. 44,45 Using transient 45 showed that PAK3 is localized at dendritic spines, and that PAK3 inactivation results in formation of abnormal dendritic spines and a reduced spontaneous synaptic activity and defective long-term potentiation (LTP). Meng et al 44 generated a knockout mice model deficient for PAK3 and showed that this model exhibits significant abnormalities in synaptic plasticity, especially hippocampal late-phase LTP, and deficiencies in learning and memory.…”
Section: Synaptic Structure and Function And Mental Retardationmentioning
confidence: 99%
“…46 For PAK3 (p21-activated kinase), a member of PAK protein family that are activated by the two small RhoGTPases Rac and Cdc42 (cell division cycle 42 ), the contribution in synapse formation and plasticity was clearly demonstrated by two groups. 44,45 Using transient 45 showed that PAK3 is localized at dendritic spines, and that PAK3 inactivation results in formation of abnormal dendritic spines and a reduced spontaneous synaptic activity and defective long-term potentiation (LTP). Meng et al 44 generated a knockout mice model deficient for PAK3 and showed that this model exhibits significant abnormalities in synaptic plasticity, especially hippocampal late-phase LTP, and deficiencies in learning and memory.…”
Section: Synaptic Structure and Function And Mental Retardationmentioning
confidence: 99%
“…Secondly, Boda et al observed that RNAi mediated suppression of PAK3, or expression of a dominant negative PAK3 mutant carrying the human MRX30 mutation, in rat hippocampal organotypic slice cultures results in the formation of abnormal elongated dendritic spines and filopodia-like protrusions, as well as a decrease in mature spine synapses. They noticed that these defects were associated with reduced expression of AMPARs at the synapse and LTP [9]. In a parallel study, Zhang et al demonstrated that PAK1 and 3 regulate spine morphogenesis by triggering the phosphorylation of MLC, the latter resulting in an increase in dendritic spine size and synapse formation [91].…”
Section: Pak3mentioning
confidence: 99%
“…This results in a regional accumulation of actin filaments which is important for the regulation of spine morphogenesis. PAK3 is highly expressed in the brain, particularly in post mitotic neurons of the cerebral cortex and the hippocampus, where it shows a diffuse distribution throughout the soma and proximal dendrites and is present in dendritc spines [9].…”
Section: Pak3mentioning
confidence: 99%
“…Hence, it is not surprising that mutations in genes encoding regulators and effectors of the Rho GTPases have been found to underlie human neurological diseases. To date, several Rho GTPase-linked genes associated with MR have been identified , including OPHN1 (Bienvenu et al, 1997;Billuart et al, 1998;Govek et al, 2004), PAK3 (Allen et al, 1998;Bienvenu et al, 2000;Boda et al, 2004;Gedeon et al, 2003;Meng et al, 2005) and ARHGEF6 (Kutsche et al, 2000;Node-Langlois et al, 2006). We embarked on the functional characterization of OPHN1.…”
Section: Introduction: Rho Gtpases Synaptic Structure and Functionmentioning
confidence: 99%